Teacher Challenges in Implementing the Independent Curriculum: Strengthening HOTS in Religious Learning - Mohammad Solihin; Andrian Wijaya (Nurul Jadid University, 2024)
This research aims to identify the challenges teachers face in implementing the Independent Curriculum, especially in strengthening higher-order thinking Skills (HOTS) in religious learning at school. The research uses a qualitative research method with the type of case study research. Data is collected through direct observation, in-depth interviews with Islamic boarding school caregivers, principals, and teachers, and analysis of related documents. The study results show that the readiness of teachers and school staff, the change in mindset from teacher-centric to student-centric, and the application of varied learning methods are the main challenges in implementing the Independent Curriculum. However, there has been an increase in students' critical thinking skills since the implementation of this curriculum. This research emphasizes the importance of ongoing support and intensive training for teachers to ensure the successful implementation of a more interactive and student-centered curriculum. The implications of this research are the need to develop educational policies that are more adaptive and responsive to the needs in the field, as well as the importance of continuous assistance to improve the quality of religious education in Indonesia.